AN ANALYSIS OF SPEECH ACTS PRODUCED BY ELEMENTARY SCHOOL TEACHERS AND STUDENTS TO FACILITATE TEACHING AND LEARNING AT SDN 10 PRINGGASELA EAST LOMBOK - ., MERDANA; K, SEKEN,; N, ADI JAYA PUTRA, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study was intended to describe, analyze, and explain types, functions, instructional functions of speech acts produced, and politeness strategies employed in the classroom. The subjects of the study were the teachers and the students. The data for this naturalistic qualitative study were collected through observation, interviews, and note taking that were then analyzed by following Miles and Hubermanâs (1994) interactive cyclical model. This study found that the teachers produced more utterances (72.59%) than students did (27.41%). The teachers mostly produced directives type of speech acts, while the studentsâ speech acts were mostly assertives namely, responses to the teachersâ directions. Furthermore, the teachers were found to use more direct directives than the indirect ones in the form of declarative, interrogative, and imperative. Those directives speech acts created in types of requestive, requirement, and advisory. The functions of the teachersâ directives were question directives, bald imperatives, embedded imperatives, need statements, hint directives, and permission directives (Tripp, 1976). The instructional functions of the teachersâ speech acts were of three modes, namely control, organization, and motivation modes (Johnson, 1997). The authority role of the teacher indicated the vertical status difference in the classroom. However, politeness linguistic devices also appeared as indication of the teacherâs efforts to reduce the imposition effect of certain acts on the students. Keywords: speech acts, teaching and learning, facilitate Â